An in situ displacement method to evaluate demulsification performance of demulsifiers. Issue 5 (25th March 2021) - Yang, Ziyi; Duan, Ming; Li, Yang; Chen, Qiming; Fang, Shenwen; Liu, Xianming
Abstract: Chemical demulsification is the most effective, common and the cheapest method to break crude oil emulsion during oil extraction. The chemical demulsification process is related with the natural emulsifier displacement by demulsifier. In this article, a single droplet in situ displacement method was employed to evaluate demulsifier displace capacity and the experimental device was built. This device determines the displacement capacity of demulsifier by measuring the oil-water interfacial tension, demulsifier concentration and saturated adsorption amount of demulsifier. Displacement capacities of four commercially available polyether demulsifiers and the relationship between demulsifier displacement capacity and demulsification performance were investigated. The results showed that the demulsifier displacement capacity was not affected by natural emulsifier type (asphaltene, resin, or mixture of asphaltene) and was related to the demulsifier type, concentration, and temperature. Demulsifier displacement capacity increased with demulsifier concentration and temperature. However, only when the asphaltene concentration of was over 6.78 wt%, the demulsification increased with demulsifier displacement capacity. Graphical Abstract: